THERMAL STABILITY OF ANTHOCYANINS FROM COMMON DOGWOOD (CORNUS SANGUINEA L.) FRUITS - MOLDOVAN, Bianca; MINTǍU, Rozalia; DAVID, Luminiţa (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The Common dogwood (Cornus sanguinea L.) fruits are known for their high antioxidant activity, partially due to their anthocyanin content. The aim of this study is to examine the storage stability of anthocyanins from these fruits, at different temperatures (2°C, 22°C and 75°C). The results show that thermal degradation reaction of anthocyanins from Common dogwood fruits complies with first-order reaction kinetics. Degradation parameters, such as half-life t1/2, reaction rate constant k and activation energy Ea values were determined. Anthocyanin extract stored at 2°C presented the highest stability with a degradation constant rate of 1.0·10-3 h-1. The calculated thermal degradation activation energy of the investigated fruits extract was Ea = 40.35 kJ/mol.